2016
DOI: 10.2337/dc16-1415
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sitagliptin on Kidney Function and Respective Cardiovascular Outcomes in Type 2 Diabetes: Outcomes From TECOS

Abstract: Impaired kidney function is associated with worse cardiovascular outcomes. Sitagliptin has no clinically significant impact on cardiovascular or CKD outcomes, irrespective of baseline eGFR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
130
3
8

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 159 publications
(151 citation statements)
references
References 28 publications
10
130
3
8
Order By: Relevance
“…Sitagliptin did not show a significant impact in delaying CKD progression against placebo with a mean eGFR decline −4.0 vs 2.8 mL/min/1.73 m 2 , respectively, with a nonsignificant UACR reductions against placebo over 4 years as well (−0.18 mg/g 95% CI: 0.32‐0.02 P = 0.032). Additionally, sitagliptin was not superior to placebo in cardiovascular outcomes …”
Section: Insulin Secretagoguesmentioning
confidence: 99%
“…Sitagliptin did not show a significant impact in delaying CKD progression against placebo with a mean eGFR decline −4.0 vs 2.8 mL/min/1.73 m 2 , respectively, with a nonsignificant UACR reductions against placebo over 4 years as well (−0.18 mg/g 95% CI: 0.32‐0.02 P = 0.032). Additionally, sitagliptin was not superior to placebo in cardiovascular outcomes …”
Section: Insulin Secretagoguesmentioning
confidence: 99%
“…In TECOS, sitagliptin was associated with a slight but sustained decrease in urine albumin‐to‐creatinine ratio over the 3‐year follow‐up period . Decreased albuminuria was also seen with saxagliptin .…”
Section: Renal Outcomes Of Dpp4 Inhibitorsmentioning
confidence: 89%
“…In a Japanese report on patients with normal renal function, the serum creatinine concentration slightly, but significantly, increased 1 month after administering sitagliptin, showing no significant difference after 24 months compared to 6 months [14]. The sub-analysis of the Trial Evaluating Cardiovascular Outcomes with Sitagliptin study (TECOS) to evaluate cardiovascular outcome in mainly normoalbuminuric T2DM patients receiving sitagliptin showed that mean change of eGFR during 48 months from the baseline was significantly lower in the sitagliptin group than in the placebo group, but the cumulative incidence of microalbuminuria and renal failure was equivalent in two groups [15]. The efficacy and safety of sitagliptin had also been reported in patients with renal failure [11][12][13].…”
Section: Discussionmentioning
confidence: 99%